Base‐Promoted Formation of an Annelated Pyrrolo‐1, 4‐oxazine Ensemble from 1H‐pyrrol‐2‐ylmethanol and Propargyl Chloride: A Theoretical and Experimental Study. Issue 1 (1st October 2019) - Vitkovskaya, Nadezhda M.; Bobkov, Alexander S.; Kuznetsova, Svetlana V.; Shcherbakova, Victoriya S.; Ivanov, Andrey V.
Abstract: A one‐pot transition‐metal‐free synthesis of pyrrolo‐1, 4‐oxazine ensemble in a KOH/DMSO superbasic medium has been developed based on the theoretical evaluation of kinetic (free activation energies) and thermodynamic (thermal effects) characteristics of the individual reaction steps. Possible interconversions of 1‐ H ‐pyrrol‐2‐ylmethanol and propargyl chloride have been addressed and the probable products of these interactions were predicted by using CBS‐Q//B3 and B2PLYP/6‐311++G**//B3LYP/6‐31+G* quantum‐chemistry approaches. Besides the target product, two other synthetically valuable compounds are synthesized with high selectivity. Abstract : A pyrrolo‐1, 4‐oxazine ensemble can be synthesized from 1 H ‐pyrrol‐2‐ylmethanol and propargyl chloride in a KOH/DMSO superbasic medium. A preliminary quantum‐chemical screening of the reaction mechanism allowed the identification of the most preferable reaction routes and products. This allowed optimization of the reaction conditions (by varying the ratio of the starting reagents, the amount of the alkali, and the degree of dilution), and three synthetically important products were obtained with high selectivity.